The Role Of Health Function Expenditure In Achieving Sdg 3 Moderated By Apip And Iepk In Indonesia - Moh Agil; Haryono Pasang Kamase; Muhammad Ikbal Abdullah; Fikry Karim (UNIVED Press, 2026)
Health is a central pillar of sustainable development and a key priority within Sustainable Development Goal 3 (SDG 3), yet Indonesia continues to face persistent health disparities across regions despite increasing public health expenditure. This study examines whether health function expenditure effectively improves SDG 3 outcomes and investigates the moderating roles of internal government supervision and corruption control. Using panel data from Indonesian provincial, district, and municipal governments for the post-pandemic period, this research applies regression and moderation analysis to assess the relationships among health expenditure, SDG 3 achievement, the capacity of the Government Internal Supervisory Apparatus (APIP), and the Effectiveness of Corruption Control Index (IEPK). The findings indicate that health function expenditure positively influences SDG 3 outcomes, and this effect is significantly strengthened when supported by effective internal supervision and strong corruption control. These results highlight that budget size alone is insufficient; governance quality plays a crucial role in translating expenditure into health improvements. The study contributes to the literature by integrating fiscal policy and governance perspectives and provides policy-relevant insights for strengthening accountability mechanisms to accelerate SDG 3 achievement in Indonesia.